Health Based Propagated Occupational Health Epidemics Associated with Overstayed and Congested Unclaimed Corpses in Public Mortuaries of Western Kenya - Silali, Maurice B.; Shaviya, Nathan; Wanzala, Maximila (British Journal of Healthcare and Medical Research, 2022)
Quality Uptake of Occupational health epidemics, in infection prevention control, measures, endure the crucial area of public health surveillance in public facility mortuaries. When handling potentially infectious unclaimed corpses, globally, regionally and locally in western Kenya, to mediate primary prevention in the health population. The main occupational hazards in public mortuaries are human remains of unclaimed corpses or clinical inpatient deaths. In additional, contaminated surrounding environment such mortuaries are also potentially harmful to the population health, due to cross infection (Contact) or inhalation. The main mortuary occupational hazards include chemical, psychosocial, biological, physical, and ergonomic hazards. While the basic biological infectious risks attributed to the exposure to congest and overstayed unclaimed corpses by mortuary and forensic service providers include, propagated pathogens of contagious biological origins, which have probability to spread by inhalation or skin contact. Such as pulmonary tuberculosis, cholera, hepatitis B & C antigens, HIV/ AIDS, and skin infections. Integument maceration by formalin and leukemia. However, though most studies, global and regional, have promulgated on the perpetual increase of occupational health epidemics, attributed to congestion and overstay on unclaimed corpses in public mortuaries. Before habitual span of 90 days of cold storage on “cold hit” of forensic investigations.Nostudieshave validated URL: http:/ / dx.doi.org/ 10.14738/jbemi.94.12539 1 British Journal of Healthcare and Medical Research (BJHMR) Vol 9, Issue 4, August - in reality, the prevalence of occupational health epidemic attributed to exposure to unclaimed corpses in public mortuaries, by mortuary and forensic service providers in western Kenya. Thus, the timely need to study Health Based Propagated occupational health epidemics Attributed to overstayed and congested unclaimed Corpse in public mortuaries. Specifically, to determine the level of occupational hazards and infectious risks attributed to overstayed and congestion of unclaimed corpses in public mortuaries and evaluate rate of professionalization of mortuary, forensic services, and essential supplies of reagent and embalmment equipment replenishment, as basic variable for sustainable health hygiene and sanitation on primary prevention in public mortuaries. Study designs, descriptive cross sectional and cohorts’ studies of mixed methods. Study populations, Primary study population, (mortuary and forensic service providers), and Secondary study population (retrospective desk review of unclaimed corpses information records) for the past 5 years (2017 -2021). Sampling designs, Active convenient purposive, and snow ball sampling, of past incidence exposure records of mortuary and forensic service providers. Data collected, by semi-structured questionnaires, retrospective review form, KII, FGDand observation guides. Data collected, spread on excel sheets before managed by SPSS version 26 for descriptive and inferences analyzes. Odds ratio (OD) and relative risk ratio (RR), determined the attributable risks in exposed and non- exposed population health. Qualitative data analyzed by categorization of themes and triangulations of verbatim. Results, out of 6 hazards propagated, majority were attributed to psychosocial hazards, 14 (22%), OD, (0.59, 0.1.7), RR (0.58). The most prevalence infection was maceration of integuments, 13 (21%), due to single uptake of gloves. No infectious epidemics recorded in the last 5 years of the retrospective desk and snowball study. Thus, the need timely need to advocate for continuous health awareness via health education and health promotion on need for health population to stop propagating on occupational health infectious disease attributed to congestion and overstay of unclaimed corpses in public mortuaries. Since they are no scientific records to support any significant outbreak attack to mortuary and forensic service providers.